PENGGUNAAN ALAT PERAGA: KEBERHASILAN BELAJAR ANAK USIA 3 – 6 TAHUN - Libertin Gea; Hari Budi Waluyo (Sekolah Tinggi Teologi Excelsius, 2020)
Abstract: The teacher understands each child specifically the learning style of children at an early age so that they can be more effective and have better relationships with students. The research approach is a case study, with the research subjects are six Kindergarten teachers at Gloria 1 Christian School Surabaya. The following research question: What is the role of using teaching aids as teaching aids for teachers in Gloria Christian school? How do teachers adjust the types of teaching aids in teaching children at Gloria Christian school? How are the children's learning outcomes using teaching aids at Gloria Christian School? The results of the study: (1) the use of teaching aids to assist teachers in teaching at Gloria Christian School is very beneficial for children and teachers who educate. (2) props in the form of real objects (pictures, videos, dolls, plants, animals), adapted to the theme to be taught at that time, props that attract children's attention and can stimulate children's cognition and psychomotor, must be kinesthetic (motion), visual (images, videos) and auditory (sound). (3) the learning outcomes of children at Gloria Christian School in using teaching aids can make it easier for children to understand the material, increase children's learning attractiveness, are able to retell, easy to remember and increase children's curiosity in learning.Abstrak: Guru memahami setiap anak secara khusus gaya belajar anak-anak pada masa usia dini sehingga ia bisa lebih efektif dan mempunyai hubungan yang lebih baik dengan murid. Pendekatan penelitian adalah studi kasus, dengan subyek penelitian adalah enam guru-guru TK sekolah Kristen Gloria 1 Surabaya. Pertanyaan penelitian berikut: Bagaimana peranan penggunaan alat peraga sebagai alat bantu mengajar guru di sekolah Kristen Gloria? Bagaimanakah guru menyesuaikan jenis alat peraga dalam mengajar anak di sekolah Kristen Gloria? Bagaimanakah hasil belajar anak dengan menggunakan alat peraga di sekolah Kristen Gloria? Hasil penelitian: (1) penggunaan alat peraga membantu guru dalam mengajar di Sekolah Kristen Gloria sangat bermanfaat bagi anak dan guru yang mendidik. (2) alat peraga yang berwujud benda nyata (gambar, video, boneka, tumbuhan, binatang), disesuaikan dengan tema yang akan diajarkan pada saat itu, alat peraga yang menarik perhatian anak dan bisa meransang kognitis serta psikomotorik anak, harus bersifat kinestetik (gerak), visual (gambar, video) dan auditory (suara). (3) hasil belajar anak di Sekolah Kristen Gloria dalam menggunakan alat peraga mampu membuat anak semakin mudah memahami materi, meningkatnya daya tarik belajar anak, mampu menceritakan kembali, mudah mengingat dan meningkatkan rasa keingintahuan anak dalam belajar.